The path(ology) less chosen: exploring medical students’ perceptions towards anatomical pathology - Budding, L.; Esterhuysen, C.; van Rooyen, C.; Goedhals, J. (South African Journal of Higher Education, 2025)
Anatomical pathologists have been described as medicine’s endangered species. The declining interest in anatomical pathology may be attributed to decreased time dedicated to undergraduate pathology teaching. In 2018, a laboratory practical session (LPS) was introduced to the undergraduate medical curriculum at the University of the Free State (UFS]), allowing students the opportunity to gain practical exposure to the discipline. The aim of this study was to investigate whether the LPS highlighted the role of anatomical pathologists in healthcare and encouraged consideration of a career in anatomical pathology. A before-and-after study was conducted among the 2021 cohort of 192 second-year medical students, of whom 176 (91.7%) participated in the survey. Questionnaires were administered before and after the LPS and participants’ responses were compared. A statistically significant improvement was observed in students’ understanding of the role of anatomical pathologists in healthcare following the LPS (p<0.0001). The LPS contributed to a 10.8 per cent (n=19) increase in the number of participants considering a career in anatomical pathology. Although the LPS improved students’ comprehension of anatomical pathologists’ role in a healthcare environment, it remains to be seen whether the success of the activity will result in increased applications for registrar positions in future (from approximately 2028/2029 for the 2021 group who participated in the survey). Only then will it be possible to ascertain from the new applicants whether the LPS experience contributed to their decision to specialise in anatomical pathology.